P1532PARATHYROID HORMONE SERUM LEVELS AND MORTALITY AMONG HEMODIALYSIS PATIENTS IN THE GULF COOPERATION COUNCIL COUNTRIES: RESULTS FROM THE DOPPS (2012-2018). (6th June 2020) - Al Salmi, Issa; Bieber, Brian; AlRukhaimi, Mona; AlSahow, Ali; Shaheen, Faissal; Al-Ghamdi, Saeed M G; Al Wakeel, Jamal; Al Ali, Fadwa; Al Arriadi, Ali; Hejaili, Fayez; Al Maimani, Yacoub; Fouly, Essam; et al.
Abstract: Background and Aims: The prospective Dialysis Outcomes and Practice Patterns Study (DOPPS) has collected data since 2012 in all six Gulf cooperation council (GCC) countries (Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, United Arab Emirates). Here, we report the relationship of PTH with mortality in this largest GCC hemodialysis patient cohort studied to date. Method: Data were from randomly-selected national samples of hemodialysis facilities in GCC DOPPS phases 5 and 6 (2012-2018). PTH descriptive findings and case-mix adjusted PTH/mortality Cox regression analyses were based on 1825 and 1422 randomly-selected hemodialysis patients, respectively. Results: Mean patient age was 55 years (median dialysis vintage = 2.1 years). Median PTH ranged from 259 pg/mL (UAE) to 437 pg/mL (Kuwait), with 22% having PTH <150 pg/mL, 24% (PTH 150-300), 34% (PTH 301-700), and 20% (PTH >700) pg/mL. Patients with PTH >700 pg/mL were younger, on dialysis longer, less likely to be diabetic, have urine>200 mL/day, prescribed 3.5 mEq/L dialysate calcium, had higher mean serum creatinine and phosphorus levels, lower white blood cell counts, and more likely to be prescribed cinacalcet, phosphate binders, or IV vitamin D. A "U-shaped" PTH/mortality relationship was observed with >2-fold and 1.5 fold higher adjusted HR of death at PTH>700 pg/mL and <300 pg/mL, respectively, compared to PTH 301-450 pg/mL. Conclusion: Secondary hyperparathyroidism is highly prevalent among GCC hemodialysis patients, with a strong U-shaped PTH/mortality relationship seen at PTH <300 and >450 pg/mL. Future studies are encouraged for further understanding this PTH/mortality pattern in relationship to unique aspects of the GCC hemodialysis population.